THE TRANSFORMATION OF AESTHETIC CRITERIA IN CLASSICAL ARABIC POETRY TO MODERN POETRY - Vionita, Mutiara Vindriani; Rapiza, Rapiza (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study analyzes the criteria of literary criticism on the beauty aspect of Arabic poetry in classical and modern contexts, focusing on the criteria of poetry beauty put forward by Ibn Qutaibah and Mahmud Sami Al-Barudi. Arabic poetry that has existed since the ignorant era is the main form of expression of the Arab nation that reflects their social, cultural, and political conditions. This study uses the work of Ibn Qutaibah entitled Asy-Syi'ru wa asy-Syu'ara' and the work of Mahmud Sami Al-Barudi entitled Al-hikam as the object of research material. The research method used is a descriptive-qualitative method, the data taken from primary data. The data collection method uses the observation method with a note-taking technique. Furthermore, the data collected by the researcher is grouped according to the existing framework. The results of this study indicate that the criteria for the beauty of poetry according to Ibn Qutaibah are very simple and objective, only covering the quality of the words and meaning, while Mahmud Sami Al-Barudi emphasizes more on the aesthetic aspects and internationalization of poetry. This study also shows that poetry not only functions as art but also as a communication tool that reflects the identity and social values of society.